Which kind of frontal mandibulotomy is the smartest? A biomechanical study. Issue 2 (March 2015) - Steiner, T.; Raith, S.; Scherer, E.; Mücke, T.; Torsiglieri, T.; Rohleder, N.H.; Eder, M.; Grohmann, I.; Kesting, M.; Bier, H.; Wolff, K.-D.; Hölzle, F.
Abstract Purpose Retrospective clinical evaluation and biomechanical tests were performed to compare the primary stability and the rate of pseudarthrosis formation after irradiation for two types of mandibular split osteotomies: the stairstep osteotomy (SSO) and the straight-line osteotomy (SLO). Methods The postoperative occurrence of pseudarthrosis was retrospectively analysed in 46 non-consecutive clinical cases of SSO and SLO between 2003 and 2013. Biomechanical tests were performed on 12 standardised synthetic mandibles (Synbone) to compare the SSO and SLO approaches. Two 2.0 mm monocortical miniplates (Medartis) were used for osteosynthesis. The artificial mandible specimens were loaded to 300 N on the Mandibulator test bench while interfragmentary motion was measured using the PONTOS optical measurement device. Results The retrospective clinical analysis showed a rate of pseudarthrosis of 19% in the SLO group versus only 5% in the SSO group (p = 0.17). In the biomechanical investigation, the average interfragmentary movement was 14.3 ± 7.70 for the SLO group and 4.57 ± 2.33 for the SSO group under a maximum load of 300 N, resulting in a statistically significant difference between the two approaches (p = 0.014). Conclusion To minimise the rate of postoperative pseudarthrosis formation, SSO is superior to SLO for mandibular split procedures, because SSO provides greater resistance to vertical loads and allows less interfragmentary movement. Level of evidence 2C (Outcomes research).